POWER SUPPLY MANAGEMENT SYSTEM DESIGN ON NODE EARLY WARNING SYSTEM FOR PEATLANDS FIRE MITIGATION - Taufiq Muammar; Rahyul Amri; Yusnita Rahayu (Universitas Mercu Buana, 2018)
Early warning system is one of the technology to detect land fires by utilizing a network of wireless sensors. Constant data transmission by the sensor nodes consumes a large amount of energy on the nodes’ sides that could affect the battery’s longevity. This research is done to discover the amount of power consumption and battery longevity during fire emergencies, and during non-emergency situation on peatlands. Power saving on the fire detecting system uses an LM35 temperature sensor, ATmega8 micro-controller and HC-12 transmission module. The overall result of powered by a 9 volt battery during fire emergencies, and during non-emergency, the power consumption reaches up to 1 Wh, with various longevity levels of the battery. The implementation of sleep/wake up mode scheduling during fire emergencies and non-emergencies could save battery for 2 hours compared to those without the power saving mode implementation. Power saving during fire emergency could be minimalized by activating the sleep mode activation power-down on the micro controller and it can also set the data transmission schedule to minimalize data usage during fire emergency, so that the usage of sleep/wake up mode interval scheduling during transmission could minimalize energy consumption and elongate the power supply active period.